Gender differences in prevalence and associations for use of CAM in a large population study - Kristoffersen, Agnete E (BMC Complement Altern Med, 2014)
BACKGROUND: Self-reported use of Complementary and Alternative Medicine (CAM) varies widely from 10% to 75% in the general populations worldwide. When limited to use of a CAM provider 2% to 49% reported use is found. CAM use is believed to be closely associated with socio demographic variables such as gender, age, education, income and health complaints. However, studies have only occasionally differentiated CAM use according to gender. Therefore, the aim of the study presented here is to describe the prevalence of CAM use on the background of gender and to describe the specific characteristics of male and female users in the total Tromsø 6 population. METHODS: A total of 12,982 men and women aged 30–87 in the municipality of Tromsø, Norway went through a health screening program and completed two self-administered questionnaires in 2007/2008. The questionnaires were developed specifically for the Tromsø study and included questions about life style and health issues in addition to socio demographic variables. RESULTS: A total of 33% of the participants reported use of any CAM within the last 12 months, women more often than men (42% and 24%, respectively). When limited to visits to a CAM provider, we found 17% use among women and 8% among men. The relationship between the demographic variables and being a CAM user differed significantly between men and women with regard to age, household income, and marital status. We did not find significant differences between men and women concerning education and self-reported health. CONCLUSIONS: Findings from this study suggest that the prevalence and associations for use of CAM differ between men and women concerning several socio demographic variables (age, education and household income). Neglect of women’s health care needs in public health care may contribute to the fact that women to a higher degree than men turn to CAM and CAM products.